ANALISIS STRATEGI PEMASARAN DIGITAL UMKM PRODUK HERBAL DI MASA PANDEMI COVID-19 (STUDI KASUS: PENGUSAHA JAMU HERBAL SINOM DI SURABAYA) Viorensa Tedjalaksana, Lucyana Trimo - Viorensa Tedjalaksana; Lucyana Trimo (Universitas Galuh, 2022)
Marketing strategy is one of the important capital for entrepreneurs for the progress of their business. An entrepreneur needs to implement the right marketing strategy in developing, especially in the digital era and the current COVID-19 pandemic. This study uses a descriptive analysis research method using the research subject of Mrs. Sariyah as an MSME entrepreneur of sinom herbal drinks in Surabaya. The data analysis technique in this study uses SWOT analysis which includes 4 aspects, namely Strengh, Weakness, Opportunity, and Threats. The results showed that the sinom herbal drink product produced by Mrs. Sariyah had several advantages that could be utilized or improved, such as strategic location, workforce skills, product quality and appropriate product prices. However, threats and product weaknesses that must be considered include the lack of licensing and halal labels from the government, the lack of cooperation in business, and the use of business technology that needs to be improved. Based on these results, it can be said that the marketing strategy of the sinom herbal drink products produced by Mrs. Sariyah is said to be quite good and needs to be improved to reach a wider market.